Loss of GCN5L1 in cardiac cells limits mitochondrial respiratory capacity under hyperglycemic conditions. Issue 8 (29th April 2019) - Thapa, Dharendra; Zhang, Manling; Manning, Janet R.; Guimarães, Danielle A.; Stoner, Michael W.; Lai, Yen‐Chun; Shiva, Sruti; Scott, Iain
Abstract: The mitochondrial acetyltransferase‐related protein GCN5L1 controls the activity of fuel substrate metabolism enzymes in several tissues. While previous studies have demonstrated that GCN5L1 regulates fatty acid oxidation in the prediabetic heart, our understanding of its role in overt diabetes is not fully developed. In this study, we examined how hyperglycemic conditions regulate GCN5L1 expression in cardiac tissues, and modeled the subsequent effect in cardiac cells in vitro. We show that GCN5L1 abundance is significantly reduced under diabetic conditions in vivo, which correlated with reduced acetylation of known GCN5L1 fuel metabolism substrate enzymes. Treatment of cardiac cells with high glucose reduced Gcn5l1 expression in vitro, while expression of the counteracting deacetylase enzyme, Sirt3, was unchanged. Finally, we show that genetic depletion of GCN5L1 in H9c2 cells leads to reduced mitochondrial oxidative capacity under high glucose conditions. These data suggest that GCN5L1 expression is highly responsive to changes in cellular glucose levels, and that loss of GCN5L1 activity under hyperglycemic conditions impairs cardiac energy metabolism. Abstract : We recently showed that the acetyltransferase‐related protein GCN5L1 was upregulated in a prediabetic high fat diet mouse model, and that this led to the acetylation of several fuel metabolism enzymes in the mitochondria. To further understand the regulatory role played by GCN5L1 under pathophysiological stress, we examined mitochondrial function under hyperglycemic conditions in vivo and in vitro. We found that GCN5L1 is downregulated under overt diabetic conditions, and that GCN5L1 depleted cells hsave reduced respiratory capacity in response to high glucose conditions.